Investigating Medication Adherence: A Mixed Methods Study - Liddelow, Caitlin Rose (Curtin University, 2021)
Caitlin’s PhD investigated the psychosocial predictors of medication adherence. She utilised a range of research designs including quantitative and qualitative methods to explore how an existing model could be applied to understand the factors which influence how people take medication as prescribed. This included a meta-analysis, interviews, and an intervention. The findings of this research provide insights into factors which may help increase medication adherence, highlighting the importance of prompts, planning, and knowledge.